Revisiting the risk of automation - Arntz, Melanie; Gregory, Terry; Zierahn-Weilage, Ulrich (Economics letters, 2017)
In light of rapid advances in the fields of Artificial Intelligence (AI) and robotics, many scientists discuss the potentials of new technologies to substitute for human labor. Fueling the economic debate, various empirical assessments suggest that up to half of all jobs in western industrialized countries are at risk of automation in the next 10 to 20 years. This paper demonstrates that these scenarios are overestimating the share of automatable jobs by neglecting the substantial heterogeneity of tasks within occupations as well as the adaptability of jobs in the digital transformation. To demonstrate this, we use detailed task data and show that, when taking into accounting the spectrum of tasks within occupations, the automation risk of US jobs drops, ceteris paribus, from 38 % to 9 %.
Available online 15 July 2017
Gesehen am 20.08.2018